Global exposure for master students - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
On May 14, 2023, the Faculty of Business and Management (FBM) welcomed a delegation from Universitas Mulawarman, organised by the International Affairs Unit and FBM Buddies, spanning from May 14 to May 21, 2023. The program included three modules- T Strategic Human Resource Development, Corporate Finance, and Corporate Leadership and Strategic Management delivered by expert speakers from our Faculty of Business and Management. We also went on an industrial visit at Tenaga Nasional Berhad (TNB) to foster a climate of perpetual learning and unparalleled sharing. We arranged a cultural event on the final day to highlight that despite our similarities, we also have differences that are valuable to showcase and exchange. This experience marks a significant milestone for our similarities setting the stage for future collaborations with delegations from diverse international backgrounds.